Scientific Revolution of family health in Chile - Parra Giordano, Denisse (2016)
Introduction. The aim of this reflection is to analyze the model change health care in Chile.Development. The conceptual framework of The Structure of Scientific Revolutions by Thomas Kuhn is analyzed by a method that compares the process of change lived in the country from a paradigm of traditional health with a strong biomedical first, until the adoption of the Model of Comprehensive Care Family health with a biopsychosocial approach, which considers the transformation process of the different actors, mainly from the Community Nursing.Conclusion. Moving health model in Chile corresponds to a Scientific Revolution. This vision of health is a pillar in nursing care and its role as a professional community health team.